Factors Influencing Mothers’ Intention to Immunize Children Younger than Five Years of Age in West Borneo: a Cross-Sectional Study - Setho Hadisuyatmana; Ilya Krisnana; Muhammad Adil Sipahutar (Jurnal Ners, 2019)
Introduction: Immunisations for BCG, DTP, Poliomyelitis, Hepatitis, and MMR are compulsory for children under 5 years old in Indonesia and government-provided free services. However, the available records indicated that adherence to the program remains a challenge. This study aimed to investigate factors associated with mothers’ intention to comply with the immunization program, particularly among those who had children of younger than one year old.Methods: The study was conducted through a cross-sectional analysis. Fourty-six mothers self-registered them selves as participants of this study. The data were collected through check-listed interviews, to investigate the correlations between social factors, information factors, attitude toward behaviour, subjective norm, perceived behavioural control, and intention to adhere to the compulsory immunization program. The data were then analysed using logistic regression and spearman rank test with significance level of α=0.05.Results: Mothers’ attitude, subjective norm, perceived behavioral control, and knowledge have significant correlations with the intention in completing the immunisation program for their children (respectively p = 0.009; 0.014; 0.025; 0.038). Their intention positively correlated with adherence to complete the program (p=0,002). However, other factors studied did not correlate either with mothers’ intention to adherence to the program.Conclusion: This study suggests that mothers’ intention is influenced by family members suggestions, indicating that their capacity in decision making was limited and relying to other member. Further investigation is required to unveil the underlying reasons of being non-adherence.